Modification and performance evaluation of a mechanical mixer for preparation of biocontrol agents used in agriculture - AJMAL T. M SHAHALA T. P; Er. Shivaji K. P (Guide) (Tavanur 2015 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Talc based bio-control agents - KCAET workshop modified mixer- user friendly
Modification and performance evaluation of a mechanical mixer for preparation of bio-control agents used in agriculture